1998
DOI: 10.1046/j.1365-2559.1998.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthokeratinized odontogenic cyst: a clinicopathological and immunocytochemical study of 15 cases

Abstract: These findings suggest that OOC is clinicopathologically separate from other types of odontogenic cysts and may thus constitute a distinct clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
101
1
18

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(131 citation statements)
references
References 26 publications
11
101
1
18
Order By: Relevance
“…Based on these findings and the diagnostic criteria proposed by the First International Colloquium on NBCCS, this patient does not have NBCCS. The findings of this case report support the findings from previous case series regarding sporadic OOC cases [1][2][3][4] that OOC does not appear to be associated with NBCCS. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on these findings and the diagnostic criteria proposed by the First International Colloquium on NBCCS, this patient does not have NBCCS. The findings of this case report support the findings from previous case series regarding sporadic OOC cases [1][2][3][4] that OOC does not appear to be associated with NBCCS. …”
Section: Discussionsupporting
confidence: 91%
“…OOC shows a different clinical behavior from OKC and most authors have concluded that it is not associated with nevoid basal cell carcinoma syndrome (NBCCS) [1][2][3][4], in which multiple OKCs are one of the major features [5]. However, all the OOC cases reported to date were sporadic cases and each patient had a single OOC.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, OKC consists of a uniform epithelial lining with a well-developed basal cell layer and a corrugated parakeratinized surface (1,4). Recent studies have discussed the histologic variants (parakeratin vs. orthokeratin) ofOKC (3,(5)(6)(7)(8)(9). Microscopically, the majority of OKC are parakeratinized OKC and orthokeratinized OKCs are only 12.2% (5).…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, the majority of OKC are parakeratinized OKC and orthokeratinized OKCs are only 12.2% (5). In addition, some investigators described that orthokeratinized OKC had clincopathologically less recurrence rate as compare with parakeratinized OKC and therefore it should be placed into a different category (5,6,8). Moreover a few researchers designated orthokeratinized OKC as orthokeratinized odontogenic cyst (OOC) (1,8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation